2011
DOI: 10.2147/phmt.s15305
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth in children with transfusion-dependent thalassemia

Abstract: Objective: To describe physical growth and related factors in transfusion-dependent thalassemia patients. Methods: This is a cross-sectional analysis of the records of the patients registered at and being followed up by the Thalassemia Day Care Center (TDCC) at Kalawati Saran Children's Hospital, New Delhi, India. Clinical and laboratory parameters were recorded on a spreadsheet for analysis. Clinical parameters included weight, height, sexual maturity ratings, and general and systemic physical examination. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 10 publications
(12 reference statements)
6
26
3
2
Order By: Relevance
“…[3]. Harish et al, (2011); also was reported that minimal siderosis, with reduced number of primordial follicles, and thickened ovarian capsules was noticed in these patients [28]. The reason for why the correlation between serum ferritin and sex hormones pattern or gonadal reserve was non-significant in this study and other studies, we can postulate that there are other etiological factors responsible for hypogonadism in these patients, the most important one is chronic persistent anemia; this can confirmed by the fact that; the single patient who had high LH post stimulation test, his Hb level was highest one.…”
Section: Discussionmentioning
confidence: 77%
“…[3]. Harish et al, (2011); also was reported that minimal siderosis, with reduced number of primordial follicles, and thickened ovarian capsules was noticed in these patients [28]. The reason for why the correlation between serum ferritin and sex hormones pattern or gonadal reserve was non-significant in this study and other studies, we can postulate that there are other etiological factors responsible for hypogonadism in these patients, the most important one is chronic persistent anemia; this can confirmed by the fact that; the single patient who had high LH post stimulation test, his Hb level was highest one.…”
Section: Discussionmentioning
confidence: 77%
“…However, other studies [38] reported significant short stature for age among their poorly chelated group (serum ferritin P2500 ng/ ml) when compared to the well chelated group (serum ferritin <2500 ng/ml) (P < 0.001). Pemde et al [39], classified their thalassemic patients into two groups, one with serum ferritin <2000 ng/ml and the other with serum ferritin >2000 ng/ ml, and they reported that the height of the patients with serum ferritin >2000 ng/ml was significantly lower than those with serum ferritin <2000 ng/ml. However, in an earlier study done in India by Gomber and Dewan [40], no relation between physical growth and serum ferritin level was found.…”
Section: Discussionmentioning
confidence: 99%
“…Physical growth is relatively normal up until 9-10 years of age but the majority of thalassemia patients fail to achieve the same final height as their normal peers [4]. Growth retardation in thalassemia is a well-observed phenomenon with a frequency between 25-66% globally [3,[5][6][7][8] and 20-57% nationally [9][10][11]. Growth retardation is multifactorial and the etiology varies with age.…”
Section: Introductionmentioning
confidence: 99%